Peningkatan Literasi Zakat bagi Masyarakat Muslim di Malaysia - Pertiwi Utami; Tejo Waskito; Nur Azizah Zuhriyah; Basrowi Basrowi (Universitas Nurul Jadid, 2024)
Al-Fateh Mosque (MMAF) - Taman Jati, Ipoh, Perak, Malaysia along with Amil Zakat and also participants of Ummatic Festival 3.0. The partner problems include Zakat literacy is still low, community participation in Zakat management is low, there is no Zakat literacy program involving mosques working with different communities, and international universities doing community service activities based on community empowerment. In relation to the three partner problems, the solutions to the problems that have been implemented include efforts to increase zakat literacy through zakat socialization, conducting zakat literacy enrichment activities for muzzaki at MMAF, and collaborating and being actively involved with MMAF, DRB-Hicom University, the ASNAF community, Islamic tourism volunteers around Ipoh and Kuala Kangsar, and several universities from Indonesia and internationally in a series of Ummatic Festival 3.0 activities. The method used in ICS activities is Participatory Action Research (PAR). After carrying out the activity; the muzzaki know the importance of paying zakat through official zakat amil institutions, the muzzaki play an active role in zakat collection and distribution activities at MMAF, and the muzzaki together with all Ummatic Festival 3.0 stakeholders were very enthusiastic to carry out ICS activities for these eight days. In addition, this program succeeded in restoring the role of the mosque as a community institution that plays a role in community activities, especially in collecting zakat for the welfare of the community.